Rebuilding the vibrational wavepacket in TRAS using attosecond X-ray pulses - Wang, Chao; Gong, Maomao; Zhao, Xi; Nan, Quan Wei; Yu, Xin Yue; Cheng, Yongjun; Kimberg, Victor; Liu, Xiao-Jing; Vendrell, Oriol; Ueda, Kiyoshi; Zhang, Song Bin (Communications Physics, 2024)
Time-resolved X-ray photoelectron spectroscopy (TXPS) is a well-established technique to probe coherent nuclear wavepacket dynamics using both table-top and free-electron-based ultrafast X-ray lasers. Energy resolution, however, becomes compromised for a very short pulse duration in the sub-femtosecond range. By resonantly tuning the X-ray pulse to core-excited states undergoing Auger decay, this drawback of TXPS can be mitigated. While resonant Auger-electron spectroscopy (RAS) can recover the vibrational structures not hidden by broadband excitation, the full reconstruction of the wavepacket is a standing challenge. Here, we theoretically demonstrate how the complete information of a nuclear wavepacket, i.e., the populations and relative phases of the vibrational states constituting the wavepacket, can be retrieved from time-resolved RAS (TRAS) measurements. Thus, TRAS offers key insights into coupled nuclear and electronic dynamics in complex systems on ultrashort timescales, providing an alternative to leverage femtosecond and attosecond X-ray probe pulses.
Published: 02 January 2024
Gesehen am 15.08.2024